2017
DOI: 10.1103/physreve.95.052132
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of diluted antiferromagnetic Ising models on frustrated lattices using the Wang-Landau method

Abstract: We use a Monte Carlo simulation to study the diluted antiferromagnetic Ising model on the frustrated lattices including the pyrochlore lattice to show the dilution effects. Using the WangLandau algorithm, which directly calculates the energy density of states, we accurately calculate the entropy of the system. We discuss the nonmonotonic dilution concentration dependence of residual entropy for the antiferromagnetic Ising model on the pyrochlore lattice, and compare it to the generalized Pauling approximation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…Magnetic ions Dy or Ho are replaced by nonmagnetic Y ions. Nonmonotonic zeropoint entropy as a function of the dilute concentration was observed experimentally, and further studies on the dilution effects have been reported [14][15][16].…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Magnetic ions Dy or Ho are replaced by nonmagnetic Y ions. Nonmonotonic zeropoint entropy as a function of the dilute concentration was observed experimentally, and further studies on the dilution effects have been reported [14][15][16].…”
mentioning
confidence: 91%
“…Magnetic ions Dy or Ho are replaced by nonmagnetic Y ions. Nonmonotonic zeropoint entropy as a function of the dilute concentration was observed experimentally, and further studies on the dilution effects have been reported [14][15][16].In this communication, we study the diluted nearestneighbor (NN) antiferromagnetic (AFM) Ising model on the pyrochlore lattice under a magnetic field in the [111] direction. We treat the NN interaction as a theoretical model; a more complicated model, such as the dipolar model, may be required to make connections to actual materials.…”
mentioning
confidence: 99%
“…In order to investigate the entropy, we use the Wang-Landau (WL) Monte Carlo method [18], which directly calculates the energy density of states (DOS), g(E). The precise estimates of the residual entropy for the diluted spin-ice model with no magnetic field were reported by Shevchenko et al [19]. If we use a canonical Monte Carlo simulation such as the Metropolis algorithm, the estimate arXiv:2108.04697v1 [cond-mat.dis-nn] 10 Aug 2021 of the entropy is obtained by the numerical integration of the specific heat.…”
Section: Introductionmentioning
confidence: 75%
“…It is impossible to realize antiferromagnetic order over the entire triangle-at least two spins are ordered ferromagnetically and at least one connection will be inevitably frustrated. Understanding the physics of frustrations is essential to understanding the properties of many materials such as spin and macrospin glasses [2,3], water ice [4,5], spin ice and artificial spin ice [6][7][8][9][10][11][12][13][14][15][16][17][18], and many others.…”
Section: Introductionmentioning
confidence: 99%